2016
DOI: 10.1007/s00122-016-2786-z
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and introgression of the wild sunflower-derived novel downy mildew resistance gene Pl 19 in confection sunflower (Helianthus annuus L.)

Abstract: A new downy mildew resistance gene, Pl , was identified from wild Helianthus annuus accession PI 435414, introduced to confection sunflower, and genetically mapped to linkage group 4 of the sunflower genome. Wild Helianthus annuus accession PI 435414 exhibited resistance to downy mildew, which is one of the most destructive diseases to sunflower production globally. Evaluation of the 140 BCF families derived from the cross of CMS CONFSCLB1 and PI 435414 against Plasmopara halstedii race 734 revealed that a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…The SNP SFW04052 and SSR ORS963 markers delimited Pl 17 in an interval of 3.0 cM. Zhang et al (2016b) reported the transfer of a new DM gene, Pl 19 from CWR H. annuus from Texas, into cultivated sunflower and mapped this gene downstream from Pl 17 in LG4. Line RHA 464, released by Hulke et al (2010b) for rust resistance based on a source derived from a CWR H. annuus population from California, was also resistant to DM with the Pl arg gene derived from H. argophyllus .…”
Section: Biotic Traitsmentioning
confidence: 99%
“…The SNP SFW04052 and SSR ORS963 markers delimited Pl 17 in an interval of 3.0 cM. Zhang et al (2016b) reported the transfer of a new DM gene, Pl 19 from CWR H. annuus from Texas, into cultivated sunflower and mapped this gene downstream from Pl 17 in LG4. Line RHA 464, released by Hulke et al (2010b) for rust resistance based on a source derived from a CWR H. annuus population from California, was also resistant to DM with the Pl arg gene derived from H. argophyllus .…”
Section: Biotic Traitsmentioning
confidence: 99%
“…Unlike BSR, DM resistance is largely governed by pathotype‐specific major genes with complete resistance. More than 20 DM resistance ( R ) genes, denoted by Pl , have been identified in sunflower conferring resistance to one or more pathotypes of P. halstedii, (Mouzeyar et al, 1995; Dußle et al, 2004; Mulpuri et al, 2009; Bachlava et al, 2011; Liu et al, 2012; Vincourt et al, 2012; Qi et al, 2015, 2016; Zhang et al, 2017; Ma et al, 2017). These R genes have been used routinely in commercial sunflower breeding programs for developing DM‐resistant hybrids.…”
mentioning
confidence: 99%
“…The wild annual H. annuus accession (PI 435414) originally collected from Paris, TX, in 1978 was used as the source of resistance to new virulent races of P. halstedii (Gulya, 2005). The DM resistance gene derived from PI 435414 was named Pl 19 and mapped to sunflower chromosome 4 corresponding to linkage group 4 (Zhang, Ma, Zhao, Markell, & Qi, 2017). The cross between CMS CONFSCLB1 and PI 435414 was made in 2013 and the selected resistant F 1 plants were backcrossed twice to CONFSCLB1.…”
Section: Methodsmentioning
confidence: 99%
“…Four single nucleotide polymorphism (SNP) markers, SFW04052, NSA_006089, C4_6675662, and S4_7964876, for Pl 19 and two SNP markers, NSA_005624 and NSA_009758, diagnostic for Pl 35 were used to confirm the presence of the R genes in HA-DM5 and HA-DM6 (Ma et al, 2019b;Qi et al, 2019;Zhang et al, 2017). DNA isolation and polymerase chain reaction analysis followed the methods described by Qi et al (2016).…”
Section: Dna Marker Testmentioning
confidence: 99%